2020
DOI: 10.1002/jmv.26412
|View full text |Cite
|
Sign up to set email alerts
|

Ocular findings in patients with coronavirus disease 2019 (COVID‐19) in an outbreak hospital

Abstract: Purpose The aim of this study was to investigate the ocular findings observed in patients with COVID‐19 caused by SARS‐CoV‐2 and to present the relationship between ocular involvement and systemic findings and laboratory results. Material and Methods This cross‐sectional study was carried out between 1 May and 30 June 2020. The study included 359 patients diagnosed with COVID‐19 and assessed by clinical evaluation, nasopharyngeal polymerase chain reaction, and lung comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(43 citation statements)
references
References 34 publications
1
42
0
Order By: Relevance
“…The majority of patients with viral conjunctivitis were male patients (Table 3). Other ocular manifestations have been documented, such as conjunctival hyperemia 25,29,31 and secretion, 25,30 conjunctival discharge, 29,31 eye rubbing, subconjunctival bleeding,…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The majority of patients with viral conjunctivitis were male patients (Table 3). Other ocular manifestations have been documented, such as conjunctival hyperemia 25,29,31 and secretion, 25,30 conjunctival discharge, 29,31 eye rubbing, subconjunctival bleeding,…”
Section: Discussionmentioning
confidence: 99%
“…12,[20][21][22][26][27][28][30][31][32] The blinding of outcome assessment (DB) is low in 12 articles. 12,[20][21][22][24][25][26][27][28][30][31][32] The incomplete outcome data (Attrition Bias) (AB) is low in 19 articles. [12][13][14][15][16][17][18][20][21][22][24][25][26][27][28][29][30][31][32] Selective reporting (Reporting bias (RB) is 16 articles.…”
Section: Independent Studies Bias Riskmentioning
confidence: 99%
See 1 more Smart Citation
“…Known ocular manifestations include conjunctivitis,[ 14 ] conjunctival hyperemia, and cotton wool spots. [ 15 ] The virus is known to spread primarily through respiratory droplets produced when an infected person coughs or sneezes. Previous studies have reported the presence of the virus in tear samples of COVID patients suggesting tears can be a source of transmission of virus.…”
Section: Discussionmentioning
confidence: 99%
“…Original article preauricular lymph nodes, and watery discharge were found to be common ocular findings in patients with active COVID-19 [5][6][7]. To the best of our knowledge, there are few studies about the possible effects of SARS-Cov-2 virus infection on the posterior segment of the eye, in the literature [8][9][10].…”
Section: Experimental Biomedical Researchmentioning
confidence: 99%